2022
DOI: 10.1021/acs.jpcc.2c04453
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenated Carbon Monolayer in Biphenylene Network Offers a Potential Paradigm for Nanoelectronic Devices

Abstract: A metallic carbon monolayer in the biphenylene network (specified as C ohs) becomes an insulator upon hydrogenation (specified as CH ohs). Patterned dehydrogenation of this CH ohs can offer a variety of intriguing functionalities. Composite structures constituted by alternating stripes of C and CH ohs with different repeat periodicity and chirality display topological properties and can form heterostructures with a tunable band-lineup or Schottky barrier height. Alternating arrangements of these stripes of fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…31,32 Regarding functionalization in biphenylene, Xie et al 15 investigated the effects of different doping concentrations of hydrogenation, fluorination, chlorination, and bromination on the electronic properties, successfully modulating biphenylene from a metal to a semiconductor. Liao et al 33 studied the energy stability of biphenylene for various hydrogenation configurations. In addition to the aforementioned hydrogenation and halogenation methods, other researchers have also investigated the effects of doping with O, C, NH 3 , CH, CO, NO 2 , and Si on the electronic properties of biphenylene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 Regarding functionalization in biphenylene, Xie et al 15 investigated the effects of different doping concentrations of hydrogenation, fluorination, chlorination, and bromination on the electronic properties, successfully modulating biphenylene from a metal to a semiconductor. Liao et al 33 studied the energy stability of biphenylene for various hydrogenation configurations. In addition to the aforementioned hydrogenation and halogenation methods, other researchers have also investigated the effects of doping with O, C, NH 3 , CH, CO, NO 2 , and Si on the electronic properties of biphenylene.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the aforementioned hydrogenation and halogenation methods, other researchers have also investigated the effects of doping with O, C, NH 3 , CH, CO, NO 2 , and Si on the electronic properties of biphenylene. 17,33,34 Previous studies have mostly focused on the effects of different doping strategies on the electronic properties of biphenylene, as well as comparisons of different doped configurations for stability. In order to fully utilize the properties of biphenylene for eventual semiconductor technology applications, further theoretical investigation is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen coverage of graphene on a single side named graphone is found to form in various patterns with different electronic and magnetic states. ,, Not only hydrogenation but also dehydrogenation of specific regions on a 2D graphane or graphone, namely, the formation of quantum antidot, were shown to induce critical modifications in their magnetic and electronic properties . Presently, an active field has emerged based on numerous experimental and theoretical studies on the patterned hydrogenation (dehydrogenation) of graphene (graphane) and recently on the fully hydrogenated carbon monolayer in the biphenylene network according to desired geometries. …”
Section: Introductionmentioning
confidence: 99%
“…The question whether the monolayers of other group IV elements, like silicene, germanene, 9,19 stanene, 20 and III−V and II−V compounds in the hexagonal network 10 stable and can undergo dramatic changes in the biphenylene network, have been addressed recently by Demirci et al 21 unveiling several important features of these 2D materials. 22,23 Now, a similar question is also valid and insofar crucial for 2H-MoS 2 being the prime member of 2D TMDs in the hexagonal network.…”
mentioning
confidence: 99%
“…Two-dimensional, nonhexagonal, monolayer of carbon in biphenylene network (B-, which consists of the connected octagon, hexagon, and square rings, also specified as the OHS structure) were predicted by earlier theoretical studies and recently synthesized using different processes. , Thus, it has been shown that the semimetallic graphene can change to a good metal in the biphenylene network as a result of the deformation of the 3-fold symmetric bonds of the carbon atoms. The question whether the monolayers of other group IV elements, like silicene, germanene, , stanene, and III–V and II–V compounds in the hexagonal network can also be stable and can undergo dramatic changes in the biphenylene network, have been addressed recently by Demirci et al unveiling several important features of these 2D materials. , Now, a similar question is also valid and insofar crucial for 2H-MoS 2 being the prime member of 2D TMDs in the hexagonal network.…”
mentioning
confidence: 99%